Síntese coloidal aquosa sustentável de pontos quânticos nanoconjugados de Ag-In-S estabilizados por carboximetilcelulose para potenciais aplicações biomédicas e ambientais - Aislan Esmeraldo Paiva (2019)
Quantum dots (QD) or semiconductor nanocrystals are within the most researched nanomaterials currently. Their attractive optical, electronic and chemical properties have wide potential in biomedical and environmental fields. The pursuit of the sustainable development implied in the design of lesser hazardous materials to the nature; considering this idea, quantum dots based on Ag, Cu, In, and S showed up as an option. Those elements have lower toxicity when compared to commonly II/IV-VI QD, such as CdS, PbS, among others. Moreover, other advantages as high reagent availability, suitable bandgap energy for several applications and photostability indicate the potential of that material group. In the present work, Ag-In-S (AIS) ternary quantum dots stabilized by carboxymethylcellulose (CMC) were synthesized. The chosen route was the aqueous colloidal chemistry at room temperature aiming sustainability, simplicity and low cost on the production of efficient fluorescent particles. It was studied the variation of pH and CMCs degree of substitution and their influence on the nucleation/growth processes of the particles. It was also examined their influence on the optical properties of absorption and emission. Superficial charge, hydrodynamic diameter and particle-ligand interaction were investigated in order to evaluate physico-chemical properties. Regarding morphology, size distribution and crystal structure were assessed. Results demonstrated the effective synthesis of AIS-nanoparticles under quantum confinement regime and stable in aqueous medium with mean size of 3.0 nm. These nanoconjugates showed emission wavelength range between 500 and 900 nm, the intensity varying according to synthesis conditions (pH 5.0 - 12.0 e DS 0.7/DS 1.2). Furthermore, the synthesis of AIS/ZnS (ZAIS) core/shell QD was carried out, the obtained quantum yield (QY) was 5.0 %, representing an increase of 70 % related to AIS QY (3.0 %). Regarding the photoluminescence decay for AIS and ZAIS QD, the lifetimes measured were 325 and 381 ns, respectively, this value being greater than values of commonly used organic dyes, such as Alexa Fluor and fluorescein. Finally, these novel nanoconjugates, free of heavy metals, demonstrated in vitro cytocompatibility and high fluorescent emission for bioimaging of normal and cancer cells. The results elucidate the potential of these quantum dots to be applied in biomedical and environmental areas, such as bioimaging and solar energy, for instance.